Women Entrepreneurship: A Systematic Review of Current Trends, Challenges, and Opportunities - Dela Cruz, Maybelle Natividad (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Today's women are better equipped than ever to carry out all activities required for a dominant portion of a community to be recognized and accepted. Every society needs women more than anything else, but they do not receive much social recognition for their commitment to community development. Although it is generally accepted that men should handle commercial matters, a considerable wage difference between men and women has been established, and independent women are regarded as having significantly less value by society. The study systematically reviewed some pieces of literature on Women Entrepreneurship: A Systematic Review of Current Trends, Challenges, and Opportunities. Women's entrepreneurship. It utilized a pragmatic research philosophy to improve the world by creating and disseminating knowledge. The literature was taken from published, peer-reviewed journals and scientifically written in English. Similarities in women's entrepreneurship were established and quoted difficulties experienced by these entrepreneurs in their endeavors. Furthermore, a few recommendations were cited to address these difficulties; hence, women's entrepreneurial development should be continuously recorded.